Sector Organization, Governance, and the Inefficiency of African Water Utilities - Estache, Antonio; Kouassi, Eugene (World Bank, Washington, DC, 2014)
The authors analyze the determinants of the efficiency levels reached by twenty one African water utilities. They assess efficiency through the estimation of a production frontier for the sector in Africa. The efficiency estimates confirm much of the common perceptions from partial productivity indicators. They point to a great heterogeneity in the African water utilities' performances, the predominance of constant returns to scale, and the great rate of technological progress. And the authors show that the institutional capacity of the country, as well as its governance quality, are significant driving factors in the performance of each firm.